(3bfHdI GdgRjeI (B:s (3OQGSGJ aj GdHQGeL GdfhhjI aj GdefWbI (B/s - (3GdYRhfj, CSYO,s 1952- ((3YeGf, GdCQOf (B:s (3OGQ OLdI fGTQhf hehRYhf,s, 2016)
(3jJfGhd GdcJGH MjK jJeMhQ Mhd GdHQGeL GdfhhjI aj efWbI GdTQb GdChSW JfGhd GdcGJH GdHQfGeL Gdfhhj GdHGcSJGfj MjK GQJcR Ydi QcjRJjf CSGSjJjf THcI Yed ddJLSS Gdfhhj hGdJgQjH jJhQW ajgG eSDhdjf ChQhHjjf dTQGA GdechfGJ hGdJbfjGJ GdCReI ddHQfGeL EVGaI Edi GdJYGhf Gdfhhj eY GdUjf dCf GdJhJQ BfPGc cGf jThH GdYdGbGJ GdHGcSJGfjI hGdUjf, hJWQb GdcGJH Gdi QOGJ GdaYd GdYGdejI GdJj cGfJ HOaY Ugjhfj(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdCSdMI GdfhhjIs -- (3GdTQb GdChSWs; (3GdCSdMI GdfhhjIs -- (3GdHdGO GdYQHjIs